Modified Method Of Dental Age Estimation Of Malay Juveniles - Safar Sumit Bunyarit; Jayakumar Jayaraman; Murali K. Naidu; Rozaida Poh Yuen Ying; Mahmoud Danaee; Phrabhakaran Nambiar (Elsevier, 2024)
Indexed by SCOPUS